Indonesia : Eleventh Review Under the Extended Arrangement. (IMF Staff Country Reports; Country Report ;, 2004)
The main priority was to seek assurances that policies were on track to facilitate a smooth transition to the postprogram environment. A stable exchange rate and continued declines in inflation have allowed reductions in interest rates in support of the economic recovery. With inflation risks now more balanced, Bank Indonesia's commitment to maintain a cautious monetary stance will help safeguard the hard-won gains on inflation and exchange rate stability. The Indonesia Bank Restructuring Agency is making good progress in bringing its asset sales programs to a successful conclusion.